MARKETING DEVELOPMENT STRATEGY FOR PACKAGED DRINKING WATER BUSINESS AT THE AQSA FACTORY IN BENER MULIE, WIH PESAM DISTRICT, BENER MERIAH REGENCY - Suci Mahara Putri; Nopri Yanto; Wahyu Isnanda Nasution (Jurnal Mahasiswa Agribisnis, 2026)
This study focuses on marketing development strategies for packaged drinking water at the Aqsa Factory in Bener Mulie, Wih Pesam District, Bener Meriah Regency. The packaged drinking water industry in Indonesia has experienced significant growth due to the increasing public awareness of health and hygiene. Despite its potential, Aqsa Factory faces challenges in expanding its market reach beyond the local area. This research employs a SWOT analysis to identify the strengths, weaknesses, opportunities, and threats affecting the business. The results show that Aqsa Factory's strengths include high-quality water sourced from the mountains, established brand recognition, and modern production technology. However, weaknesses such as limited product innovation and marketing management hinder its growth. Opportunities lie in the increasing demand for quality drinking water and the potential for partnerships with distributors and hotels. Conversely, threats from intense competition and economic uncertainty pose challenges. Recommended strategies include leveraging strengths to exploit opportunities, such as enhancing marketing efforts through social media and expanding product variants. By implementing these strategies, Aqsa Factory can improve its market position and achieve sustainable growth in the packaged drinking water industry.